(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The article is a legal comparative approach where legal entities of the continental and the Anglo-Saxon legal family are subject of legal investigation. Its main peculiarities in legal status, criteria of classification and functional purpose are examined. Special focus is made on the development of the concept of a legal entity: historically it passed the way of debates on the nature of the legal entity (the so-called fictional and realistic theory), and reached to the actual trends of regulation. The activities of this institution concerning the legal systems of post-Soviet states and adaptation to new economic conditions are explored. The author suggests that by means of the comparative analysis, it is possible to not only define the systemic divergences between the two legal families, but also define the most adequate ways to regulate the activity of the legal entities realizing the significant state functions. The study can lead to the improvement of corporate and administrative legislation through the study results.